"It just seems like people are talking about menopause, but nobody has a solution": A qualitative exploration of menopause experiences and preferences for weight management among Black women. (March 2022) - Kracht, Chelsea L.; Romain, Jessica St.; Hardee, Julie C.; Santoro, Nanette; Redman, Leanne M.; Marlatt, Kara L.
Highlights: Black women feel unprepared for changes they experience during menopause. Weight gain and difficulty losing weight from menopause are major concerns for women. Women want to learn about different diets and exercises for healthy living. Women want to learn more about menopause alongside other women. Social support, accountability, and seeing results are perceived components for lasting behavioral change. Abstract: Objectives: A qualitative study was performed to characterize experiences of women going through menopause, as well as to identify barriers and facilitators for participating in a lifestyle program targeting weight management during menopause. Study Design: Perimenopausal and postmenopausal Black women with a self-reported desire to lose or maintain weight during menopause participated in a total of six focus groups. Main Outcome Measures: Women were asked about their past experiences with diet, exercise, and weight management; their menopause experiences; as well as specific components and considerations for developing a lifestyle program for weight management. Thematic analysis was conducted on coded transcripts and four main themes emerged, each containing three to seven subthemes. Results: Twenty-seven Black women (age 54±4 years, BMI 35.1 ± 9.0 kg/m 2 ) were enrolled. Overall, women felt unprepared for the changes they experienced during menopause and had difficulty maintaining or losing weight. While women were receptive to trying different diets and exercises, they wanted a diet that was flexible with their lifestyle and exercises that considered their existing health status. Women were also interested in learning about menopause alongside other women, stating that medical professionals did not provide them with adequate information or help. Social support, accountability, and seeing results were perceived critical to achieve long-lasting behavioral change. Conclusions: Women were interested in receiving menopause information and improving their overall health as part of a lifestyle program during menopause. Associating with other women affected by menopause will allow for the creation of more sustainable lifestyle programs during menopause. Clinicaltrials.gov identifier: NCT04487782.